2012
DOI: 10.4314/ajtcam.v9i3s.8
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Complementary and Alternative Medicine: Knowledge, Attitudes and Practices of Health Care Workers in HIV and Aids Clinics in Durban Hospitals

Abstract: Traditional complementary and alternative medicine (TCAM) has been reported to be commonly used among individuals with HIV and AIDS disease. However a lack of communication between health care workers (HCWs) and patients as well as between HCWs and TCAM practitioners has been identified as one of the challenges that may adversely affect treatment of HIV and AIDS patients. With improved and sustained communication HCWs, patients and TCAM practitioners would be able to make informed decisions with regards to bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…Various studies have reported the use of HM in health subpopulation [30][31][32][33] and in different locations and settings. [33][34][35] General population use of HM similar to this study has been reported in South Africa, 36 Benin, 37 Uganda 38 and Nigeria. 18 39 40 But the prevalence of HM use in the general population is sparse in sub-Saharan Africa.…”
Section: Discussionsupporting
confidence: 83%
“…Various studies have reported the use of HM in health subpopulation [30][31][32][33] and in different locations and settings. [33][34][35] General population use of HM similar to this study has been reported in South Africa, 36 Benin, 37 Uganda 38 and Nigeria. 18 39 40 But the prevalence of HM use in the general population is sparse in sub-Saharan Africa.…”
Section: Discussionsupporting
confidence: 83%
“…Forestry harvested food items, nuts and indigenous fruits can greatly reduce vulnerability to hunger and malnutrition among rural inhabitants. Considering that many rural inhabitants are poor and cannot afford the cost of allopathic medicines, forests are crucial for medicinal products including bark, bulbs, leaves and roots (Akinnifesi et al, 2007;Gqaleni et al, 2007).…”
Section: Importance Of Forestry and Conservation Forestry To South Af...mentioning
confidence: 99%
“…Another Durban-based study amongst health care workers in HIV and/or AIDS clinics reflected poor CAM knowledge including those of homeopathy and CHM (Mbutho, Gqaleni & Korporaal 2012). Australian pharmacists also reported a lack of knowledge about CAM and its safety and identified it as a definite barrier to their recommendations; however, they still did so together with conventional medicine as part of the pharmacy protocol (Culverhouse & Wohlmuth 2012).…”
Section: Knowledge or Familiaritymentioning
confidence: 99%
“…Another South African study noted that the pharmacological knowledge of herbal medication was limited in pharmacists, and the respondents felt they were ill-equipped to advise patients to the best of their ability (Brijlal et al 2011). In a local study (Mbutho et al 2012), it was mentioned that a lack of communication between patient and health care practitioner on CAM choices could increase the potential risk of the patient because of exposure to adverse effects; and according to the WHO ( 2008), the lack of communication negatively impacts on the patient not making an informed decision regarding medical treatment options available to them (World Health Organization 2008). This is because they have partial, fragmented or unreliable information (Mbutho et al 2012).…”
Section: Communicationmentioning
confidence: 99%